Development for Sustainable Agriculture The Brazilian Cerrado - Hosono, Akio.; Rocha, Carlos Magno Campos da.; Hongo, Yutaka; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Since the mid-1970s, the tropical savanna, known as Cerrado, has been transformed into one of the world's largest grain-growing regions. This book explores how and by what Brazil achieved inclusive and sustainable growth in the Cerrado.
Keywords: Sustainable development; Economic policy; Ethnology-Latin America; Economic development; Agriculture; Development Policy; Latin American Culture; Development Studies